2023
DOI: 10.1007/s11356-023-25596-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of machine learning algorithms for groundwater quality modeling

Abstract: Groundwater quality is measured through water sampling, and lab analysis. The eld-based measurements are costly and time-consuming when applied over a large domain. In this study, we developed a machine learning-based framework to map groundwater quality in an uncon ned aquifer in the north of Iran. Groundwater samples were provided from 248 monitoring wells across the region. The groundwater quality index (GWQI) in each well was measured and classi ed into four classes of Very poor, Poor, Good, and Excellent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Further, the outcomes of the study have been suggested that the ensemble ML algorithms has been utilized to estimate and determine the WQI with accuracy. A ML-based framework has been developed in [25], to map the quality of groundwater in an released aquifer in North Iran. In this study, groundwater samples have been conferred from 248 monitoring wells through the area of North Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, the outcomes of the study have been suggested that the ensemble ML algorithms has been utilized to estimate and determine the WQI with accuracy. A ML-based framework has been developed in [25], to map the quality of groundwater in an released aquifer in North Iran. In this study, groundwater samples have been conferred from 248 monitoring wells through the area of North Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The advancement of machine learning (ML) methods has garnered significant attention due to their robust algorithms, which can greatly enhance the predictive capabilities of models. Among ML approaches, tree-based algorithms, such as XGBoost, CatBoost, and LightGBM, have been successfully applied to develop QSAR models in environmental fields. , These algorithms have been applied in various fields, such as to retrieve daily PM2.5 concentrations, evaluate groundwater quality, and design adsorbent materials . Additionaly, they have been used for predicting the k of SO 4 •– , HClO, O 3 , and ClO 2 .…”
Section: Introductionmentioning
confidence: 99%